Effect of liquid-phase surface tension on hydrodynamics of a three-phase airlift reactor with an enlarged degassing zone - Freitas, Carla Maria Duarte de (1998)
[Excerpt] Airlift reactors are especially useful for operations requiring solid-suspension without high shear force (e.g. fermentation and cell culture). Fermentation broths are complex mixture of cells, sugars, electrolytes, proteins, etc. and exhibit high viscosity, low surface tension and non-Newtonian characteristics [1]. However, the majority of hydrodynamic data for airlift reactors has been obtained with air/water systems, with properties different from the real conditions of operation. It is, nevertheless, known that both liquid viscosity and surface tension affect gas holdup. The small bubbles formed in liquids with reduced surface tension may enhance gas holdup. It is considered that dilute aqueous alcohol solutions simulate reasonably well the liquid-phase behaviour in bioreactors [2], being the surface tension the only physical property which differs significantly from water. Aqueous solutions of ethanol represent a coalescence inhibiting system, which will affect bubble size and the overall hydrodynamics. The aim of this study is to compare the behaviour of a three-phase airlift reactor (60 l), of the concentric draught-tube type, with an enlarged degassing zone when water and an aqueous solution of ethanol are used as liquid-phase. The concentration of ethanol used (10 g/l) is higher than the limiting concentration (0.11 mol/l) reported by Zahradník et al. [3], in order to observe the maximum deviation possible. Ca-alginate beads were used as solid-phase. Gas and solids holdup in the riser and in the downcomer, circulation and mixing times and riser and downcomer interstitial liquid velocity were measured for both liquid-phases, changing solids loading (0% to 30% (v/v) and airflow rate (from 1.9 to 90.2 l/min). […]